Heavy Metal Concentrations in Sediment Cores from Different Mangrove Forests in Da Loc Commune, Hau Loc District, Thanh Hoa Province, Vietnam - Minh, Tran Thi; Tai Tue, Nguyen; Dang Quy, Tran (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 3, 2018)
Abstract : In order to clarify heavy metal concentration profiles in different mangrove forest ages, four sediment cores (up to 100 cm in depth) were collected and tested for their physicochemical characteristics (pH, Eh, organic matters and grain size) and heavy metal concentrations. Results showed that mangrove sediments were composed mainly of sandy silt, silty sand, silt, sandy mud and mud. The average mud content in the sediment cores continuously increased with mangrove forest ages from one, nine, nineteen and twenty years old, whereas the mud content highly fluctuated with the core depth. pH, Eh and organic matter content implied that the sedimentary depositional environments were classified as weak alkaline and anaerobic. The Cu and Zn concentrations in the sediment cores from the intertidal zone exceeded the TEL values in Canadian Interim Marine Sediment Quality Guideline (ISQGs) values, while, Pb concentration exceeded the PEL level. When compared with National Technical Regulation on Sediment Quality QCVN43:2012/BTNMT, sediment samples were polluted by Cu and Pb. Keywords: Mangrove sediments, heavy metals, intertidal, Da Loc. References [1]   D. M. Alongi, “Carbon payments for mangrove conservation: Ecosystem constraints and uncertainties of sequestration potential”, Environ. Sci. Policy, vol. 14, no. 4, pp. 462–470, 2011. [2]   D. M. Alongi, “Mangrove forests: Resilience, protection from tsunamis, and responses to global climate change”, Estuar. Coast. Shelf Sci., vol. 76, pp. 1–13, 2008. [3]   M. Lewis, R. Pryor, and L. Wilking, “Fate and effects of anthropogenic chemicals in mangrove ecosystems: A review”, Environmental Pollution. pp. 2328–2346, 2011. [4]   Z.-W. Zhang, X.-R. Xu, Y.-X. Sun, S. Yu, Y.-S. Chen, and J.-X. Peng, “Heavy metal and organic contaminants in mangrove ecosystems of China: A review”, Environ. Sci. Pollut. Res., vol. 21, no. 20, pp. 11938–11950, 2014. [5]   N. F. Y. Tam and Y. S. Wong, “Retention and distribution of heavy metals in mangrove soils receiving wastewater”, Environ. Pollut., 1996. [6]   K. Yunus et al., “Heavy Metal Concentration in the Surface Sediment of Tanjung Lumpur Mangrove Forest, Kuantan, Malaysia”, Sains Malaysiana, vol. 40, no. 2, pp. 89–92, 2011. [7]   N. T. Tue, N. T. Ngoc, T. D. Quy, H. Hamaoka, M. T. Nhuan, and K. Omori, “A cross-system analysis of sedimentary organic carbon in the mangrove ecosystems of Xuan Thuy National Park, Vietnam”, J. Sea Res., 2012. [8]     K. Abou Seedo, M. S. Abido, A. A. Salih, and A. Abahussain, “Assessing Heavy Metals Accumulation in the Leaves and Sediments of Urban Mangroves (Avicennia marina (Forsk.) Vierh.) in Bahrain”, Int. J. Ecol., 2017. [9]     L. H. Defew, J. M. Mair, and H. M. Guzman, “An assessment of metal contamination in mangrove sediments and leaves from Punta Mala Bay, Pacific Panama”, Mar. Pollut. Bull., 2005. [10]   S. Costa-Böddeker and C, “Ecological risk assessment of a coastal zone in Southern Vietnam: Spatial distribution and content of heavy metals in water and surface sediments of the Thi Vai Estuary and Can Gio Mangrove Forest”, Mar. Pollut. Bull., vol. 114, no. 2, pp. 1141–1151, 2017. [11]   D. D. Kurlapkar and S. D. Shaikh, “Original Research Article Sediment characteristics of mangroves from Bhatey and Kalabadevi Estuary (Maharashtra), India”,  Int.J.Curr.Microbiol.App.Sci, vol. 3, no. 6, pp. 449–453, 2014. [12]   H. Agah, H. M.S, and W. Baeyen, “Trace Metals and Major Elements in Sediments of the Northern Persian Gulf”, J. Persian Gulf, vol. 3, no. 7, pp. 45–58, 2012. [13]   S. Orchard, L. C. Stringer, and W. P. No, “Exploring mangrove social-ecological system dynamics in South-East Asia: linking livelihoods, vulnerability and ecosystem services in Vietnam”, Clim. Chang. Econ. Policy Work. Pap. No.169, no. 169, 2014. [14]   S. E. Orchard, L. C. Stringer, and C. H. Quinn, “Mangrove system dynamics in Southeast Asia: linking livelihoods and ecosystem services in Vietnam”, Reg. Environ. Chang., vol. 16, no. 3, pp. 865–879, 2016. [15]   S. E. Orchard, L. C. Stringer, and C. H. Quinn, “Impacts of aquaculture on social networks in the mangrove systems of northern Vietnam”, Ocean Coast. Manag., vol. 114, pp. 1–10, 2015. [16]   S. L. T. Hoa, “Adapting to Natural Disasters and Contributing to Climate Change Mitigation: Mangrove Community Forestry in Vietnam”, Link. Adapt. Mitig. through Community For. Case Stud. from Asia, p. 80, 2012. [17]   N. T. Tue, L. V. Dung, M. T. Nhuan, and K. Omori, “Carbon storage of a tropical mangrove forest in Mui Ca Mau National Park, Vietnam”, Catena, vol. 121, pp. 119–126, 2014. [18]   R. L. Folk, “The Distinction between Grain Size and Mineral Composition in Sedimentary-Rock Nomenclature”, J. Geol., 1954. [19]   Q. Tu, S. Yang, Q. Zhou, and J. Yang, “Sediment transport and carbon sequestration characteristics along mangrove fringed coasts”, Acta Oceanol. Sin., vol. 34, no. 2, pp. 21–26, 2015. [20]   M. F. Adame, D. Neil, S. F. Wright, and C. E. Lovelock, “Sedimentation within and among mangrove forests along a gradient of geomorphological settings”, Estuar. Coast. Shelf Sci., vol. 86, no. 1, pp. 21–30, 2010. [21]   M. D. Hossain and A. A. Nuruddin, “Soil and mangrove: A review”, J. Environ. Sci. Technol., vol. 9, no. 2, pp. 198–207, 2016. [22]   V. Hatje, T. E. Payne, D. M. Hill, G. McOrist, G. F. Birch, and R. Szymczak, “Kinetics of trace element uptake and release by particles in estuarine waters: Effects of pH, salinity, and particle loading”, Environ. Int., vol. 29, no. 5, pp. 619–629, 2003. [23]   M. Z. Hossain, C. B. Aziz, and M. L. Saha, “Relationships between Soil Physico‐Chemical Properties and Total Viable Bacterial Counts in Sunderban Mangrove Forests, Bangladesh”, Dhaka Univ. J. Biol. Sci., vol. 21, no. 2, pp. 169–175, 2012. [24]   S. Das, “Depth Integrated Microbial Community and Physico-Chemical Properties in Mangrove Soil of Sundarban, India”, Adv. Microbiol., vol. 2, no. 3, pp. 234–240, 2012. [25]   L. H. N. Cooper, “Oxidation-Reduction Potential in Sea Water”, J. Mar. Biol. Assoc. United Kingdom, vol. 22, no. 1, pp. 167–176, 1937. [26]   F. E. S. Ghada and D. H. Youssef, “Ecotoxicological impact assessment of some heavy metals and their distribution in some fractions of mangrove sediments from Red Sea, Egypt”, Environ. Monit. Assess., vol. 185, no. 1, pp. 393–404, 2013. [27]   A. R. A. Usman, R. S. Alkredaa, and M. I. Al-Wabel, “Heavy metal contamination in sediments and mangroves from the coast of Red Sea: Avicennia marina as potential metal bioaccumulator”, Ecotoxicol. Environ. Saf., 2013. [28]   G. R. MacFarlane, “Leaf biochemical parameters in Avicennia marina (Forsk.) Vierh as potential biomarkers of heavy metal stress in estuarine ecosystems”, Mar. Pollut. Bull., vol. 44, no. 3, pp. 244–256, 2002. [29]   L. Perdomo, I. Ensminger, L. F. Espinosa, and C. Elster, “The Mangrove Ecosystem of the Ci enaga Grande de Santa Marta ( Colombia ): Observations on Regeneration and Trace Metals in Sediment”, vol. 37, 1999. [30]   S. P. Kumar and J. K. Patterson Edward, “Assessment of metal concentration in the sediment cores of Manakudy estuary, south west coast of India”, Indian J. Mar. Sci., vol. 38, no. 2, pp. 235–248, 2009. [31]   R. Chowdhury, P. J. C. Favas, M. P. Jonathan, P. Venkatachalam, P. Raja, and S. K. Sarkar, “Bioremoval of trace metals from rhizosediment by mangrove plants in Indian Sundarban Wetland”, Mar. Pollut. Bull., vol. 124, no. 2, pp. 1078–1088, 2017. [32]   S. Caeiro et al., “Assessing heavy metal contamination in Sado Estuary sediment: An index analysis approach”, Ecol. Indic., vol. 5, no. 2, pp. 151–169, 2005. [33]   J. Stendahl, B. Berg, and B. D. Lindahl, “Manganese availability is negatively associated with carbon storage in northern coniferous forest humus layers”, Sci. Rep., vol. 7, no. 1, pp. 1–6, 2017. [34]   E. P. Nobi, E. Dilipan, T. Thangaradjou, K. Sivakumar, and L. Kannan, “Geochemical and geo-statistical assessment of heavy metal concentration in the sediments of different coastal ecosystems of Andaman Islands, India”, Estuar. Coast. Shelf Sci., vol. 87, no. 2, pp. 253–264, 2010. [35]   K. K. Turekian and K. H. Wedepohl, “Geological Society of America Bulletin Distribution of the Elements in Some Major Units of the Earth's Crust”, Geol. Soc. Am. Bull., vol. 72, pp. 175–192, 1961. [36]   Canadian Council of Ministers of the Environment, “Canadian Sediment Quality Guidelines for the Protection of Aquatic Life”, Environ. Prot., pp. 1–3, 2001.